Z Marcellem Venezianim o bogach i tęsknocie za nimi (recenzja). - Grzeszczak, Jan (Poznańskie Studia Teologiczne, 2021)
This review article is an attempt to introduce the Polish reader to the most important aspects of Marcello Veneziani’s book Nostalgia degli dei. Una visione del mondo in dieci idee (The longing for gods: Vision of the world in ten ideas), published in 2019. The Italian author, philosopher, journalist, writer and TV commentator, addresses the problem of diseases plaguing contemporary Western civilization that threaten its further existence. The book is a proposal to return to metaphysical thinking, but in a way akin to a contemporary pop version, and Veneziani’s gods, close to Platonism, are metaphors and ‘penultimate deities’: Civilisation, Homeland, Family, Community, Tradition, Myth, Fate, Soul, God and Return. The article provides a subjective review of the content of Veneziani’s book and juxtaposes it with Joseph Ratzinger’s famous proposal addressed to contemporary non-believers, that is, ‘to live as if God existed’ (veluti si Deus daretur).